Clergy Renewal: The Alban Guide to Sabbatical Planning - Bullock, Richard; Bruesehoff, Richard (Rowman & Littlefield Publishers, 2000)
Planned time away from the parish for study, rest, and spiritual renewal can be beneficial-and often necessary-for any pastor, as well as for the congregation. In this thoroughly revised and expanded edition of Alban’s popular Sabbatical Planning for Clergy and Congregations, Bullock and Bruesehoff provide the definitive guide to putting together refreshing pastoral sabbaticals that can help keep ministry vital and growing for the long term